INCREASING STUDENTS' LEARNING ENGLISH LANGUAGE THROUGH THE TASK-BASED LEARNING METHOD IN CLASS X AT SMA YPPGI SINAKMA WAMENA PAPUA PEGUNUNGAN - Kogoya, Napius; Sem, Adriana (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Abstract This research was conducted to evaluate the effectiveness of the Task-Based Learning (TBL) method in enhancing the English language learning outcomes of Great students at SMA YPPGI Sinakma, Wamena, Papua Pegunungan. The study employed a quantitative approach, utilising a pre-experimental design featuring a one-group pre-test and post-test model. A total of 30 students were selected as the sample through purposive sampling. Data collection instruments included pre-tests, post-tests, classroom observations, and student questionnaires. The findings indicated that the Task-Based Learning method significantly enhanced students’ English proficiency. The average pre-test score of 58.2 rose to 78.6 in the post-test, reflecting an overall mean improvement of 20.4 points. Statistical analysis via a sample t-test confirmed a significant difference between the pre-test and post-test results at the 0.05 significance level. Furthermore, observational and questionnaire data revealed that students exhibited increased motivation, confidence, and active engagement during the learning process. The results demonstrate that Task-Based Learning effectively promotes students’ English learning by fostering meaningful communication, collaboration, and practical language use. Consequently, it can be concluded that the TBL method is a suitable and effective teaching strategy for enhancing English proficiency among high school students, particularly in remote learning contexts such as SMA YPPGI Sinakma Wamena.